Activation of GCN2 in macrophages promotes white adipose tissue browning and lipolysis under leucine deprivation. Issue 6 (18th May 2021) - Wang, Fenfen; Xiao, Fei; Du, Linjuan; Niu, Yuguo; Yin, Hanrui; Zhou, Ziheng; Jiang, Xiaoxue; Jiang, Haizhou; Yuan, Feixiang; Liu, Kan; Chen, Shanghai; Duan, Shengzhong; et al.
Abstract: We have previously shown that leucine deprivation stimulates browning and lipolysis in white adipose tissue (WAT), which helps to treat obesity. Adipose tissue macrophages (ATMs) significantly influence WAT browning and lipolysis. However, it is unclear whether ATMs are involved in leucine deprivation‐induced browning and lipolysis in WAT; the associated signals remain to be elucidated. Here, we investigated the role of ATMs and the possible mechanisms involved in WAT browning and lipolysis under leucine‐deprivation conditions. In this study, macrophages were depleted in mice by injecting clodronate‐liposomes (CLOD) into subcutaneous white adipose tissues. Then, mice lacking general control nonderepressible 2 kinase (GCN2), which is a sensor of amino acid starvation, specifically in Lyz2‐expressing cells, were generated to investigate the changes in leucine deprivation‐induced WAT browning and lipolysis. We found leucine deprivation decreased the accumulation and changed the polarization of ATMs. Ablation of macrophages by CLOD impaired WAT browning and lipolysis under leucine‐deprivation conditions. Mechanistically, leucine deprivation activated GCN2 signals in macrophages. Myeloid‐specific abrogation of GCN2 in mice blocked leucine deprivation‐induced browning and lipolysis in WAT. Further analyses revealed that GCN2 activation in macrophages reduced the expression of monoamine oxidase A (MAOA), resulting in increased norepinephrine (NE) secretion from macrophages to adipocytes, and this resulted in enhanced WAT browning and lipolysis. Moreover, the injection of CL316, 243, a β3‐adrenergic receptor agonist, and inhibition of MAOA effectively increased the level of NE, leading to the enhancement of browning and lipolysis of WAT in myeloid GCN2 knockout mice under leucine deprivation. Collectively, our results demonstrate a novel function of GCN2 signals in macrophages, that is, regulating WAT browning and lipolysis under leucine deprivation. Our study provides important hints for possible treatment for obesity.